Long-term Monocyte Dysfunction after Sepsis in Humanized Mice Is Related to Persisted Activation of Macrophage-Colony Stimulation Factor (M-CSF) and Demethylation of PU.1, and It Can Be Reversed by Blocking M-CSF In Vitro or by Transplanting Naïve Autologous Stem Cells In Vivo - Lapko, Natalia; Zawadka, Mateusz; Polosak, Jacek; Worthen, George S.; Danet-Desnoyers, Gwenn; Puzianowska-Kuźnicka, Monika; Laudanski, Krzysztof (Frontiers in Immunology, 2017)
The duration of post-sepsis long- term immune suppression is poorly understood. Here, we focused on the role of monocytes (MO) as the pivotal cells for long-term regulation of post-sepsis milieu. Lost ability of MO to adapt is seen in several acute conditions but it is unclear for how long MO aberrancy post-sepsis can persist. Interestingly, the positive feedback loop sustaining secretion of macrophage colony stimulation factor (M-CSF) can persist even after resolution of sepsis and significantly alters performance of MO. Here, we investigated the activation of M-CSF, and its critical regulator of PU.1 in mice surviving 28 days after sepsis. Our primary readout was the ability of monocytes (MO) to differentiate into dendritic cells (DC; MO→iDC) in vitro since this is one of the critical processes regulating a successful transition from innate to acquired immunity. We utilized a survival modification of the cecal ligation and puncture model of sepsis (CLP) in humanized mice. Animals were sacrificed 28 days after CLP (tCLP+28d). Untouched (CONTR) or sham operated (SHAM) animals served as controls. Some animals received rescue from stem cells originally used for grafting two weeks after CLP. We found profound decrease of MO→iDC in the humanized mice 28 days after sepsis, demonstrated by depressed expression of CD1a, CD83, and CD209, diminished production of IL-12p70, and depressed ability to stimulate T cells in mice after CLP as compared to SHAM or CONTR. In vitro defect in MO→iDC was accompanied by in vivo decrease of BDCA-3+ endogenous circulating DC. Interestingly, post-CLP MO had persistent activation of M-CSF pathway, shown by exaggerated secretion of M-CSF, activation of PU.1, and demethylation of SPII. Neutralization of the M-CSF in vitro reversed the post-CLP MO→iDC aberration. Furthermore, transplantation of naïve, autologous stem cells derived MO restored CLP-deteriorated ability of MO to become DC, measured as recovery of CD1a expression, enhanced production of IL-12p70, and ability of IL-4 and GM-CSF MO to stimulate allogeneic T cells. Our results suggest the role of epigenetic mediated M-CSF aberration in mediating post-sepsis immune system recovery.